Neuroinflammation and Brain Functional Disconnection in Alzheimer’s Disease - Baglio, Francesca; Saresella, Marina; Preti, Maria G.; Cabinio, Monia; Griffanti, Ludovica; Marventano, Ivana; Piancone, Federica; Calabrese, Elena; Nemni, Raffaello; Clerici, Mario (Frontiers in Aging Neuroscience, 2013)
Neuroinflammation and brain functional disconnection result from β-amyloid (Aβ) accumulation and play fundamental roles in the pathogenesis of Alzheimer’s disease (AD). We investigated possible correlations between these two AD-associated phenomena using DTI-based tractography and immunologic analyses in people with amnestic mild cognitive impairment (aMCI) and AD. DTI-Analyses focused on corpus callosum (CC). We found that frontal CC regions were preserved with respect to the posterior ones in aMCI; in these individuals significant correlations were seen between DTI-derived metrics in frontal-parietal CC areas and Aβ42-stimulated BDNF-producing CD4+ T lymphocytes and PDL-1-expressing CD14+ cells. These associations were lost in AD where DTI data involving the same CC areas correlated instead with Aβ42-stimulated interleukin (IL)-21 producing CD4+ T lymphocytes. Higher susceptibility to PDL-1-mediated apoptosis of Aβ42-specific lymphocytes and BDNF-associated survival of existing neurons could contribute to the relative CC structure preservation seen in aMCI. These potentially protective mechanisms are lost in frank AD, when severe alterations in the CC are mirrored in peripheral blood by proinflammatory cytokines-producing T cells. Monitoring of immune cells in peripheral blood could have a prognostic value in AD.